2016
DOI: 10.1177/1533034616643884
|View full text |Cite
|
Sign up to set email alerts
|

Gelsolin Promotes Radioresistance in Non–Small Cell Lung Cancer Cells Through Activation of Phosphoinositide 3-Kinase/Akt Signaling

Abstract: Gelsolin is an actin-binding protein and acts as an important regulator of cell survival. This study aimed to determine the function of gelsolin in the radioresistance of non-small cell lung cancer cells. We examined the expression of gelsolin in radioresistant A549 and H460 cells and their parental cells. The effects of gelsolin overexpression and knockdown on the clonogenic survival and apoptosis of non-small cell lung cancer cells after irradiation were studied. The involvement of phosphoinositide 3-kinase/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Gelsolin is characterized as an actin-binding protein and favors malignant progression of multiple tumor cells such as non-small lung cancer, gastric carcinoma, and glioma. 27 , 49 , 50 More importantly, several reports have indicated that Gelsolin facilitates tumor cells progression by regulating various cellular key pathways, including phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK). 50 , 51 PI3K/Akt and MAPK are two classical pathways that directly regulate cell proliferation, migration, invasion, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gelsolin is characterized as an actin-binding protein and favors malignant progression of multiple tumor cells such as non-small lung cancer, gastric carcinoma, and glioma. 27 , 49 , 50 More importantly, several reports have indicated that Gelsolin facilitates tumor cells progression by regulating various cellular key pathways, including phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK). 50 , 51 PI3K/Akt and MAPK are two classical pathways that directly regulate cell proliferation, migration, invasion, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that PI3K/Akt signaling pathway is activated in a wide range of tumors, the activated PI3K/Akt is associated with progression, invasion, metastasis in multiple tumor types [24]. Akt activation is associated with radioresistance in some malignant tumors such as head and neck cancer, prostate cancers, non-small cell lung cancer and cervical cancer [25][26][27][28]. Mechanistically, PI3K-Akt induces radioresistance by enhancing aerobic glycolysis, accelerating repair of IR-induced DNA double-strand breaks (DNADSB), activating tumor-cell proliferation and attenuating radiation-induced apoptosis [27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Evidences suggest that GSN may act as a tumor suppressor gene, indeed, several studies showed a GSN down-regulation in human cancers including breast carcinoma [44,46]. Notably, Wang and colleagues in 2014 reported that GSN may regulate the sensitivity to chemotherapy in patients with head-and-neck cancer [47], whereas more recently Zhao and colleagues have reported the GSN involvement in radio-resistant LC patients [48]. In support of this, Li and colleagues demonstrated a protective role of GSN against radiation-induced secondary injury in mice, by promoting the tissue regeneration [49].…”
Section: Discussionmentioning
confidence: 99%